Створення Харківської міської лікувально-санітарної організації як впливовий чинник поліпшення якості життя містян наприкінці XIX – на початку XX століть - Робак, Ігор Юрійович; Демочко, Ганна Леонідівна (Дніпровський національний університет імені Олеся Гончара, 2024)
У статті розглядається вплив удосконалення медичної допомоги й санітарного впорядження в Харкові наприкінці ХІХ – на початку ХХ століть на якість життя його мешканців. Метою статті є доведення того факту, що створення міської лікувально-санітарної організації стало потужним чинником поліпшення якості життя харківців. У статті категорія «якість життя» пов’язується із сучасними науковими концепціями HRQoL і Urban Health. Пристосовуючи сучасні показники цих концепцій до соціальної історії медицини Харкова, автори аналізують, як з історичним поступом міської охорони здоров’я і поліпшенням санітарного стану змінювались пов’язані з ними характеристики громадського здоров’я, головні з яких є одночасно й характеристиками якості життя. Дотепер науковці не розглядали історико-медичні проблеми Харкова саме в такому ключі. Стаття теоретична, має історико-медичний характер, проте охоплює широке міждисциплінарне поле. Міждисциплінарний характер розвідки наклав відбиток на використання методів дослідження. В ньому суто історичні та краєзнавчі методи інтегруються з методами тих наук, що входять до цієї міждисциплінарної предметної галузі (медичних, економічних, демографії, екології, географії). Простеживши зміну таких показників якості життя, як забезпеченість населення лікарями, середнім медичним персоналом, аптечними послугами, чисельність лікарів і середнього медичного персоналу, рівень смертності, медико-екологічні характеристики, автори дійшли висновку, що зі створенням у тогочасному Харкові модерної моделі надання медичної допомоги населенню і санітарного впорядження міста якість життя його мешканців суттєво поліпшилась.

This article explores the impact of enhancing medical care and sanitation in Kharkiv on the residents’ quality of life during the late XIX and early XX centuries. The purpose of the article is to prove that the creation of the city medical and sanitary organisation was a powerful factor in improving the quality of life of Kharkiv residents. The article connects the contemporary concept of “quality of life” with modern scientific notions like Health-related Quality of Life (HRQoL) and Urban Health, aligning them with Kharkiv’s historical retrospective review in the late XIX and early XX centuries. As a result, by adapting modern indicators of the above concepts to the social history of medicine in Kharkiv, the authors analyse how, with the historical change of urban environment factors or city characteristics (in particular, the progress of urban health care and improvement of the sanitary state), the associated characteristics of public health changed accordingly. And major characteristics simultaneously represents the quality of life. The theoretical article, characterized as historical and medical, however, embraces an interdisciplinary approach, incorporating methods from philosophy, economics, sociology, psychology, demography, cultural studies, political science, education, ecology, geography and law. Thus far, neither domestic nor foreign historians have examined the historical and medical issues of Kharkiv in such way, and this non-standard approach is the study scientific novelty. The study interdisciplinary nature left its mark on the research methods used. It integrates purely historical and regional methods with sciences being a part of this interdisciplinary subject area. The authors examine various quality of life indicators, such as the availability of doctors, nurses, pharmacy services, the number of doctors and nurses and mortality rates, concluding that the establishment of a modern medical care model in the existed Kharkiv led to an improvement in quality of life during that period. The study also delves into the sanitary aspects, including waste management, drinking water quality, water bodies, water protection, and working conditions, revealing positive changes following the creation of the city sanitary organization. The article emphasizes that contemporary medical and environmental indicators might not fully capture past quality of life changes, as they fail to address previously overcome issues like unsanitary conditions in public places, food quality (especially meat), extensive use of livestock in industry, transport, and trade, wood heating, and manual labour without safety precautions. The authors assert that steady sanitary progress occurred in Kharkiv in these areas as well. Grounded in reliable historical sources, the article establishes that the formation of the Kharkiv city medical and sanitary organization significantly enhanced the quality of life for the city’s residents during the late XIX and early XX centuries.
The Kharkiv city medical and sanitary organization: a driving force in enhancing the quality of life for residents in the late XIX and early XX centuries
Keywords: HRQoL; Urban Health; краєзнавство; лікувально-санітарна організація; соціальна історія медицини; Харків; якість життя; local study; medical and sanitary organization; social history of medicine; Kharkiv; quality of life